2022
DOI: 10.3847/1538-4357/ac6b9a
|View full text |Cite
|
Sign up to set email alerts
|

Nodal Precession and Tidal Evolution of Two Hot Jupiters: WASP-33 b and KELT-9 b

Abstract: Hot Jupiters orbiting rapidly rotating stars on inclined orbits undergo tidally induced nodal precession measurable over several years of observations. The Hot Jupiters WASP-33 b and KELT-9 b are particularly interesting targets because they are among the hottest planets found to date, orbiting relatively massive stars. Here, we analyze archival and new data that span 11 and 5 yr for WASP-33 b and KELT-9 b, respectively, in order to model and improve upon their tidal precession parameters. Our work confirms th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The best-fit eccentricity value agrees with a circular orbit only at 4 σ. Furthermore, Stephan et al (2022) recently found a nodal precession trend using radial velocity measurements, which could also have an effect on the transit timings, albeit generally a much smaller signal in comparison to apsidal precession for typical hot Jupiters. Transit duration variations are a better indicator for nodal precession (Miralda-Escudé 2002;Ragozzine & Wolf 2009;Damiani & Lanza 2011).…”
Section: Timing Analysismentioning
confidence: 99%
“…The best-fit eccentricity value agrees with a circular orbit only at 4 σ. Furthermore, Stephan et al (2022) recently found a nodal precession trend using radial velocity measurements, which could also have an effect on the transit timings, albeit generally a much smaller signal in comparison to apsidal precession for typical hot Jupiters. Transit duration variations are a better indicator for nodal precession (Miralda-Escudé 2002;Ragozzine & Wolf 2009;Damiani & Lanza 2011).…”
Section: Timing Analysismentioning
confidence: 99%
“…We consider this discrepancy more likely real, and possibly indicative of a pre-eclipse-post-eclipse asymmetry. We exclude that this is caused by the nodal precession of KELT-9b (Stephan et al 2022), which would only change the inclination of the orbit by about 1 • in three years and whose effect on K p would be at the 10 −4 level. We return to our interpretation of the variation of K p in the following section and in section 4.3.…”
Section: Confirmation Of Iron Emission Lines From the Dayside Of Kelt-9bmentioning
confidence: 99%
“…We note here that given the high impact parameter for the transit of TOI-640 b, any change in orbital inclination caused by for example nodal precession (see e.g. Szabó et al 2012;Johnson et al 2015;Watanabe et al 2020Watanabe et al , 2022Stephan et al 2022) may be picked up by future photometric (TESS) observations.…”
Section: Refined Parameters For Toi-640 Bmentioning
confidence: 89%